Comparing the cost-benefit of breast cancer screening programs in rural and urban areas across four economic zones in China: a Markov modeling analysis - Dachuang Zhou; Kejia Zhou; Wenjuan Wang; Hanqiao Shao; Hongliu Zhang; Wenxi Tang (BMC Public Health)
Abstract Background This study assessed the effectiveness and cost-effectiveness of breast cancer screening across rural and urban regions in China’s four economic zones. Methods Using a decision-analytic Markov model, we evaluated 5,280 scenarios involving different ages and screening technologies. The model followed individuals from birth through 100 yearly cycles in eight settings. Model parameters, such as incidence, transition rate, attendance and compliance rate, screening accuracy, utility, and mortality, were based on Chinese research and international data. Screening costs were calculated using median medical costs in the respective zones. The main outcome measured was incremental net benefit (INB) and incremental cost-effectiveness ratio (ICER), with sensitivity analyses to assess uncertainty. Results Using a willingness-to-pay threshold of three times the local per capita Gross domestic product (GDP), the recommended strategies varied across regions. However, annual screening of individuals aged 30–70 years with a combination of mammography (MAM) and computed tomography laser mammography (CTL) was the most cost-effective strategy for most regions. The incremental cost-effectiveness ratios (ICERs) of the most cost-effective strategies, compared to no intervention and status quo in China, ranged from US$5,173.31/QALY to US$18,551.27/QALY, and from US$-3,872.28 to US$17,804.59, respectively. Except for the rural central region, where the cost-effective strategy had suboptimal outcomes compared to status quo, the recommended strategies in the other seven regions could prevent 41.12–58.80% and 8.08–35.39% of advanced breast cancer cases, and 18.83–29.27% and 2.71–14.06% of breast cancer deaths, when compared to no screening and status quo, respectively. Sensitivity analysis indicated that the results were robust. Conclusion Our study identified cost-effective breast cancer screening strategies suitable for the rural and urban areas in China’s four major economic zones. These findings highlight the necessity of universal screening and the importance of optimizing strategies based on regional economic development and epidemiological characteristics. These insights are crucial for improving national breast cancer screening policies.